Population-level cure of colorectal cancer in Malta: An analysis of patients diagnosed between 1995 and 2004. (June 2016) - Gauci, Dorothy; Allemani, Claudia; Woods, Laura
Highlights: We analyse short and long term survival of colorectal cancer in Malta. We use mixture model with Weibull survival distribution to model 'cure'. We see an improvement in long and short term survival over 15 years. Age at diagnosis associated with both short and long term survival. Abstract: Aim: The aim of this study was to estimate the population-level 'cure' of Maltese colorectal cancer patients diagnosed between 1995 and 2004, and to estimate the median survival time for the 'uncured' patients. Methods and study population: Analysis was conducted on 1470 cases registered by the Malta National Cancer Register between 1995 and 2004 and followed up to end of 2010. The mean age of the patients was 66.4 (95%CI 65.8–67.1), and the number of men and women were equal. Background mortality for 1995–2010 was extracted from publicly available life tables. A mixture model with Weibull survival distribution and identity link was used to model 'cure'. Results: The overall 'cured' proportion for the patients diagnosed in 1995–1999 was 45.3% (95%CI 40.2–50.5) while the 'cured' proportion for the patients diagnosed in 2000–2004 was 52.3% (95%CI 47.2–57.5). Median survival time for the 'uncured' patients increased in the second calendar period from 1.25 years (95%CI 1.04–1.45) to 1.42 years (95%CI 1.15–1.76). Conclusion: In Malta, as in the rest of Europe, improvements have been made in short- and long-term survival over the 15-year period under study. To continue this improvement, differences by age that still persist must be investigated and efforts focused to reduce any gaps between Malta and other European countries.